Evaluation of the presence of microorganisms in solid-organ preservation solution - Mattana, André Marcelo Colvara; Marra, Alexandre Rodrigues; Machado, Antônia Maria de Oliveira; Lopes Filho, Gaspar de Jesus [UNESP]; Salzedas Netto, Alcides Augusto; Gonzalez, Adriano Miziara (Brazilian Society of Infectious Diseases, 2011)
OBJECTIVE: To assess the presence of microorganism contamination in the preservation solution for transplant organs (kidney/pancreas). Method: Between August 2007 and March 2008, 136 samples of preservation solution were studied prior to graft implantation. Variables related to the donor and to the presence of microorganisms in the preservation solution of organs were evaluated, after which the contamination was evaluated in relation to the recipient culture variable. Univariate and multivariate statistical analyses were performed. RESULTS: The contamination rate of the preservation solution was 27.9%. Coagulase-negative Staphylococcus was the most frequently isolated microorganism. However, highly virulent agents, such as fungi and enterobacteria, were also isolated. In univariate analysis, the variable donor antibiotic use was significantly associated to the contamination of the preservation solution. on the other hand, multivariate analysis found statistical significance in donor antibiotic use and donor's infectious complications variables. CONCLUSIONS: In this study, 27.9% of the preservation solutions of transplant organs were contaminated. Infectious diseases and non-use of antibiotics by the donor were significantly related to the presence of microorganisms in organ preservation solutions. Contamination in organ preservation solutions was not associated with infection in the recipient.
Keywords: Organ transplantation; Disease transmission, infectious; Organ preservation solutions; Microbial viability